1980
DOI: 10.3402/tellusa.v32i1.10481
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide measurements in the eastern tropical Pacific Ocean

Abstract: In March 1976 the first N,O measurements were made in the sea water and marine air of the eastern tropical Pacific Ocean during a cruise from San Diego, California, to San Martin, Peru. Continuous measurements of N,O in the marine atmosphere were made throughout the duration of the cruise. The tropospheric mixing ratio was 332 f 9 p.p.b. v/v N,O. The concentration of N,O in the marine air appeared to show a direct relationship to the N,O concentration in the surface sea water, with the highest N,O mixing ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…This reduction of nitrate to ammonium is most likely to be carried out by phytoplankton in the marine environment and has been suggested as an alternative source of N20 in the surface ocean. The studies of Hahn [1981], Pierotti and Rasmussen, [1980] and Oudot et al [1990] invoke this mechanism to account for very high surface N20 levels in upwelling zones. There is, however, no direct support for such conclusions, and Goteau et al [1980] found no evidence of N20 release from cultures of phytoplankton; furthermore, Cohen and Gordon [1979] note that if such a source exists, it is probably of relatively small magnitude.…”
Section: Main Cycling Processesmentioning
confidence: 99%
“…This reduction of nitrate to ammonium is most likely to be carried out by phytoplankton in the marine environment and has been suggested as an alternative source of N20 in the surface ocean. The studies of Hahn [1981], Pierotti and Rasmussen, [1980] and Oudot et al [1990] invoke this mechanism to account for very high surface N20 levels in upwelling zones. There is, however, no direct support for such conclusions, and Goteau et al [1980] found no evidence of N20 release from cultures of phytoplankton; furthermore, Cohen and Gordon [1979] note that if such a source exists, it is probably of relatively small magnitude.…”
Section: Main Cycling Processesmentioning
confidence: 99%
“…Oceanic N 2 O has been widely studied since the 1960s, and its basic distribution patterns in the Atlantic Ocean [Junge and Hahn, 1971], the Pacific Ocean [Butler et al, 1989;Cline et al, 1987;Codispoti and Christensen, 1985;Cohen and Gordon, 1978;Pierotti and Rasmussen, 1980;Singh et al, 1979;Yoshida et al, 1984], and the Arabian Sea [Bange et al, 1996;Naqvi and Noronha, 1991] have been well described. N 2 O emission hotspots such as the Eastern Tropical Pacific and the Arabian Sea were discovered during this period, and their significant contributions to the global N 2 O budget have been comprehensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, some uncertainties remain as to the role of nitrification in N20 formation in aquatic environments. AOU is merely a measure of the total biological oxygen utilization and oxidation of ammonium or organic amines accounts for only a minor part of the oxygen consumption (PIEROTTI and RASMUSSEN, 1980 ) .…”
Section: Introductionmentioning
confidence: 99%